Development Intelligent Agent in Educational Game “Pesut Adventure – Borneo Animal Match-Up” with Shuffle Random Algorithm - Aulia Khoirunnita; Bartolomius Harpad; Nurul Ikhsan; Reza Andrea; Husmul Beze; Rudito Rudito (Politeknik Pertanian Negeri Samarinda, 2023)
Research developing Edu-game ”Pesut Adventure – Borneo Animal Educational Game” is a research develop Match-Up type game. In this type game, player must find match 2 images of the Borneo animals in the same time, the player must remember the position of the image to be matched. The shuffling-random algorithm used to make images position always scrambled and player never get bored playing. AI technology (artificial intelligence) is also applied on this research. Using the Finite State Machine (FSM) model, the game agent was created in funny-animals form. It will mentoring the children to play this game like a teacher